Arqueología Incluyente: Weaving Diverse Narratives in Northwestern Mexican Archaeology. Issue 3 (August 2022) - Martínez-Tagüeña, Natalia; Sánchez, Guadalupe; Carpenter, John; Torres Cubillas, Luz Alicia; Vélez, Leopoldo
Abstract: In Mexico, archaeological heritage belongs to all members of society, according to section XXV of Article 73 of the Mexican Constitution and Article 27 of the federal law on monuments and archaeological sites. The Instituto Nacional de Antropología e Historia (INAH) was founded in 1939 as a federal government agency for the research, protection, and dissemination of archaeological heritage. Although this heritage belongs to all, stringent rules and procedures create an unequal relationship between career professionals and the diverse communities interested in the past (i.e., collectors, local museums, descendant communities). It is long due to begin practicing an inclusive archaeology that considers all the various knowledge systems (i.e., academic, technical, local, and traditional) of the communities interested in the past. Here, we describe case studies from Sonora, Mexico, to propose the implementation of several far-reaching activities with artifact collectors, Indigenous communities, researchers, archaeologists, and INAH Sonora authorities. Our pilot proposal needs to be implemented in other areas of Mexico that continue to prioritize archaeological narratives over other narratives about our past.